2011
DOI: 10.1248/bpb.34.1493
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin from Dioscorea nipponica Ameliorates Diabetic Neuropathy by Inducing Nerve Growth Factor

Abstract: The increasing prevalence of diabetes heightens concerns over diabetic complications such as neuropathy. Diabetic neuropathy is one of the most debilitating complications of type 1 and type 2 diabetes.1) The histopathology of the condition is characterized by axonal degeneration, demyelination, and atrophy in association with failed axonal regeneration, remyelination, and impaired synaptogenesis. 2)Previous reports have suggested that reduced availability of nerve growth factor (NGF) plays a significant role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…Axon demyelination and loss were also presented in the sciatic nerve of diabetic mice by electron microscopy examination (Kang et al, 2011). The proper function and maintenance of axons depended on myelin formation (Lappe-Siefke et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Axon demyelination and loss were also presented in the sciatic nerve of diabetic mice by electron microscopy examination (Kang et al, 2011). The proper function and maintenance of axons depended on myelin formation (Lappe-Siefke et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidences showed that NGF played a significant role in the pathogenesis of diabetic polyneuropathy, and itself had been considered an option for the treatment of diabetic peripheral pain 12 . In our study, we confirmed the expression of NRG1 and NGF in spinal cord of rats.…”
Section: Nrg1 Treatment Increased Ngf Level In Spinal Cordmentioning
confidence: 99%
“…Retrograde axonal transport of NGF is impaired in animals with DM, and its transcription in neuronal target tissues is reduced. Pathological conditions that alter NGF expression may result in neuronal dysfunction and death 12 . A previous study showed that the concentration of NGF in the sciatic nerves of STZ-induced diabetic rats decreased 3 weeks after STZ injection 23 .…”
Section: Exogenous Nrg1 Can Inhibit Diabetic Neuropathic Painmentioning
confidence: 99%
“…In particular, D. japonica has inhibitory activities on polyuria and diabetes (Kim, 1998) and D. nipponica has antiobesity properties (Jung et al, 2003). Previously, we reported that furostanol saponins isolated from D. japonica upregulated NGF contents in rat glioma C6 cells (Kim et al, 2011a) and diosgenin from D. nipponica ameliorated diabetic neuropathy by increasing the endogenous NGF levels in streptozotocin (STZ)-induced diabetic mice (Kang et al, 2011). Therefore, we proposed that these two Dioscorea species might improve various symptoms of diabetic neuropathy via NGF regulation.…”
Section: Original Articlementioning
confidence: 99%
“…The NCV tests were performed using the methods reported by Kang (Kang et al, 2011). Animals were anesthetized using a combination of 1.5% isofluorane (Choongwae Pharma Co., Seoul, Korea) with 70% N 2 O and 30% O 2 gas using a gas anesthesia machine (Tabletop research anesthesia machine sets, SurgiVet, USA).…”
Section: Measurements Of Nerve Conduction Velocity In Motor and Sensomentioning
confidence: 99%